2021
DOI: 10.1177/08862605211037420
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Sexual Abuse and Exposure to Peer Bullying Victimization

Abstract: Females exposed to child sexual abuse (CSA) are at an increased risk of experiencing further victimization in adolescence. Associations between CSA and several forms of cyber and in-person peer bullying victimization were assessed in a prospective, longitudinal study. Females exposed to substantiated CSA and a matched comparison group (N = 422) were followed over a two-year period. Bullying experiences were assessed in both survey and qualitative interviews. Qualitative data were coded and used to describe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
0
2
1
Order By: Relevance
“…Previous studies have also noted signi cant gender differences in the effects of childhood trauma on peer victimization. A prospective study reported that females who suffered child sexual abuse were at increased risk of peer victimization compared to males [74]. However, in the present study, no gender differences were found, which may be due to the unbalanced ratio of males to females in the current study sample.…”
Section: Discussioncontrasting
confidence: 85%
“…Previous studies have also noted signi cant gender differences in the effects of childhood trauma on peer victimization. A prospective study reported that females who suffered child sexual abuse were at increased risk of peer victimization compared to males [74]. However, in the present study, no gender differences were found, which may be due to the unbalanced ratio of males to females in the current study sample.…”
Section: Discussioncontrasting
confidence: 85%
“…Previous studies have noted significant gender differences in the effects of childhood trauma on peer victimization. A prospective study reported that females who suffered child sexual abuse were at increased risk of peer victimization compared to males [ 98 ]. However, some studies also found that there are no gender differences in physical violence in childhood trauma, i.e., both boys and girls who are physically abused in childhood are at increased risk of peer intimidation and physical assault in adolescence [ 99 ].This could be explored further in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown CSA survivors to be more likely to display high-risk internet behaviors, including choosing provocative self-representations online, and being exposed to sexual content online (Maas et al, 2019, Noll et al, 2009, 2013. Lastly, in line with CSA survivors being at an increased risk of subsequent revictimization, including peer victimization and bullying, they have also been shown to be at heightened risk for cyberbullying victimization online (Kennedy et al, 2021). This might reflect social and emotional developmental vulnerabilities, making CSA survivors more likely to be bullied for their actions and how they present themselves.…”
Section: Understanding Heterogeneity In Trajectoriesmentioning
confidence: 99%